FAMILY BASED SOCIAL CAPITAL IN HANDLING OF COVID-19 PREVENTION IN BLITAR DISTRICT - Kusnul Khotimah; Sarmini Sarmini; Ali Imron (University of Muhammadiyah Malang, 2020)
Indonesia is currently entering a non-natural disaster emergency response phase in the coronavirus pandemic case (Covid-19). Handling during this crisis will determine whether the number of positive cases of Covid-19 will continue to increase or be controlled. Community solidarity can move the Indonesian people together against Covid-19. Finally, social capital is expected to be a social weapon to overcome the Covid-19 disaster. Based on the phenomena written in the background of the problems mentioned above, this study will examine comprehensively and integrated with encouraging the creation of a model of strengthening family-based social capital in dealing with the prevention of Covid-19. This study uses qualitative research methods, the presentation of data from this study uses a descriptive format. The results of this study are social capital in the form of cooperation and participation between citizens so far as a form of social interaction that is beneficial for the prevention of Covid-19 prevention. The village government develops village innovation by calling Endhong Indhit Village, which is to help one another, cooperation among citizens with the dominance of nuclear family and extended family. The purpose of Endhong Indhit Village is that no residents will be disturbed during this pandemic.